1995
DOI: 10.1111/j.1751-1097.1995.tb08619.x
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine Fluorescence at High Concentration: Dimers or Reabsorption Effect?

Abstract: For tetrasulfonated aluminum phthalocyanine (AlPcS,), dimer formation is characterized in the absorption spectrum by a broadening of the Q-band and the appearance of a new band at the red edge of the spectrum. The high concentrations required to produce dimers, however, often leads to anomalous observations in fluorescence spectroscopy. In the present study, we have examined the photophysical characteristics of two dye systems; AlPcS, in a 66% ethanovwater mixture and disulfonated aluminum phthalocyanine in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
159
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 22 publications
5
159
1
2
Order By: Relevance
“…To test the importance of selfabsorption in the fluorescence quenching phenomenon, we simulated PL spectra (ESIw) according to a literature model. 17 The simulated and experimental spectra agreed only for blends with very low dye concentrations (below 1 wt%), meaning that self-absorption alone is not able to explain the pronounced quenching. A decrease of PL intensity with increasing chromophore concentration has been observed in other dyes as well.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…To test the importance of selfabsorption in the fluorescence quenching phenomenon, we simulated PL spectra (ESIw) according to a literature model. 17 The simulated and experimental spectra agreed only for blends with very low dye concentrations (below 1 wt%), meaning that self-absorption alone is not able to explain the pronounced quenching. A decrease of PL intensity with increasing chromophore concentration has been observed in other dyes as well.…”
Section: Discussionmentioning
confidence: 90%
“…A decrease of PL intensity with increasing chromophore concentration has been observed in other dyes as well. 17,18,29 Most photophysical studies were made in solution 19,30 and often these conclusions cannot be transferred to the condensed state. In solution, one of the main non-radiative pathways for excited-state deactivation is cis-trans photo-isomerization and/or the formation of a twisted intramolecular charge transfer state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With very few exceptions, neither MPc dimers nor higher order cofacial aggregates fluoresce (47)(48)(49). Electronic adsorption spectra of MPc's can provide insight into groundstate aggregation processes (50); a split and blue-shifted Q-band typically indicates cofacial ground-state aggregation of Pc rings (19,44,46,51,52).…”
Section: Spectral Properties Of the Mpc-oligonucleotide Conjugatesmentioning
confidence: 99%
“…Nevertheless, we observe that, since the host-guest interactions can strongly affect the dye fluorescence efficiency, measuring the quantum yield of both organic-inorganic and organic-organic fluorescent nanoparticules is of paramount importance for the development of any optophotonic application. Unfortu-nately, although the optical properties and the fluorescence efficiency of most organic dyes are reported in the literature 45 and/or can be easily measured in solution, 46,47 very few systematic and quantitative studies on the quantum yield of fluorescent nanopigments can be found in the literature 18,19 and a precise measurement is often lacking. On one hand, the relative quantum yield is indeed commonly estimated by comparison with a well-know fluorescent agent in solution taken as reference.…”
Section: Introductionmentioning
confidence: 99%